In weak statistical control?. (25th April 2007) - Chakhunashvili, Alexander; Bergman, Bo
There are usually two distinct objectives to attain a process in statistical control, including economic aspects, and predictability. While both objectives are important from a statistical quality control standpoint, they do not necessarily have to be fulfilled simultaneously. In this paper, we suggest a generalisation of the concept 'in statistical control' especially useful for processes in which assignable causes of a certain kind are found, but their presence do not jeopardise the predictability (within limits) of the process. Such processes are referred in this paper as processes in weak statistical control.